Assessment of the professional environment of anesthesia nurses - Rozgaitė, Giedrė (Slauga. Mokslas ir praktika, 2021)
Abstract. The professional environment for nurses is attracting international interest, as there is a growing consensus that maintaining high-quality care, job satisfaction for nurses and staff retention are essential to identify opportunities to improve working conditions in hospitals. Improving the practice environment, including the patient-nurse relationship, requires maintaining the skilled and dedicated work of nurses, reducing burnout and job dissatisfaction among nurses, and benefiting patients in terms of better quality care. Nurses ’perceptions of their professional environment affect their job satisfaction.
Keywords: nursing leadership; nursing practice; professional environment